Relacje pomiędzy strukturami własnościowymi a strategiami rozwoju polskich spółek akcyjnych - zarys koncepcji badawczej - Bohdanowicz, Leszek; Jeżak, Jan; Matyjas, Zbigniew (The relationship between ownership structures and growth strategies of Polish corporations - the outline of research project, 2006)
In the paper the authors describe the theoretical background and the outline of their research project concerning the potential connections between ownership structures and growth strategies of Polish companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 191-199